Vertical distributions of radionuclides along the tourist‑attractive Marayon Tong Hill in the Bandarban district of Bangladesh - Siraz, M. M. Mahfuz; Roy, Debasish; Dewan, Md. Jafor; Alam, M. S.; M., Jubair A.; Rashid, Md. Bazlar; Khandaker, Mayeen Uddin *; Bradley, D.A. *; Yeasmin, S. (Springer, 2023)
This is the first attempt in the world to depict the vertical distribution of radionuclides in the soil samples along several heights (900 feet, 1550 feet, and 1650 feet) of Marayon Tong hill in the Chittagong Hill Tracts, Bandarban by HPGe gamma-ray spectrometry. The average activity concentrations of 232Th, 226Ra, and 40K were found to be 37.15 ± 3.76 Bqkg−1, 19.69 ± 2.15 Bqkg−1, and 347.82 ± 24.50 Bqkg−1, respectively, where in most cases, 232Th exceeded the world average value of 30 Bqkg−1. According to soil characterization, soils ranged from slightly acidic to moderately acidic, with low soluble salts. The radium equivalent activity, outdoor and indoor absorbed dose rate, external and internal hazard indices, external and internal effective dose rates, gamma level index, and excess lifetime cancer risk were evaluated and found to be below the recommended or world average values; but a measurable activity of 137Cs was found at soils collected from ground level and at an altitude of 1550 feet, which possibly arises from the nuclear fallout. The evaluation of cumulative radiation doses to the inhabitants via periodic measurement is recommended due to the elevated levels of 232Th.This pioneering work in mapping the vertical distribution of naturally occurring radioactive materials (NORMs) can be an essential factual baseline data for the scientific community that may be used to evaluate the variation in NORMs in the future, especially after the commissioning of the Rooppur Nuclear Power Plant in Bangladesh in 2024.